Endodontic management of pulp canal obliteration using a new single-tooth template: A case series - Natanasabapathy Velmurugan; Sathish Sundar; Parashar Saumya-Rajesh; Kinnari Kasabwala; D P Shilpa-Jain; Sarath Sarathy; Keerthana Prabakaran; J S Haritha; Lars Bjørndal (Wolters Kluwer Medknow Publications, 2021)
Background: Guided Endodontics is suggested as a reliable method for management of teeth with pulp canal obliteration (PCO). The guide used for this usually involves multiple teeth to gain stability but is bulky. It is therefore suboptimal to be used along with rubber dam. Aim: To describe the use of a minimized single-tooth guide template in three patients with radiographic evidence of PCO. Design: The template was designed and fabricated using the cone-beam computed tomography (CBCT) scan and a surface scan image of the involved teeth. In all three patients, the root canals were successfully negotiated within 15 minutes, with the template involving only the tooth in focus or with neighboring half of the teeth. The operator stabilized the template if required. Conclusions: This case series shows clinically that successful outcome can be obtained during guided endodontics with the use of a single-tooth template in previously traumatized anterior teeth with PCO.